2000
DOI: 10.1038/35017536
|View full text |Cite
|
Sign up to set email alerts
|

The sedimentary structure of linear sand dunes

Abstract: Linear sand dunes--dunes that extend parallel to each other rather than in star-like or crescentic forms--are the most abundant type of desert sand dune. But because their development and their internal structure are poorly understood, they are rarely recognized in the rock record. Models of linear dune development have not been able to take into account the sub-surface structure of existing dunes, but have relied instead either on the extrapolation of short-term measurements of winds and sediment transport or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
179
1
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(198 citation statements)
references
References 8 publications
12
179
1
6
Order By: Relevance
“…Ainda na costa do Rio de Janeiro, radarfácies semelhantes foram descritas por Moulton et al (2013), num estudo sobre a gê-nese e morfologia de dunas frontais. Cabe ressaltar trabalhos precursores de GPR associados à fácies eólicas, como Bristow et al (2000aBristow et al ( , 2000b.…”
Section: Arquitetura Deposicionalunclassified
“…Ainda na costa do Rio de Janeiro, radarfácies semelhantes foram descritas por Moulton et al (2013), num estudo sobre a gê-nese e morfologia de dunas frontais. Cabe ressaltar trabalhos precursores de GPR associados à fácies eólicas, como Bristow et al (2000aBristow et al ( , 2000b.…”
Section: Arquitetura Deposicionalunclassified
“…This reconstruction showed that with lateral migration taken into account, linear dune internal structures could look remarkably like those of transverse dunes (Rubin and Hunter, 1985). Bristow et al (2000) used ground penetrating radar (GPR) in combination with OSL and found evidence for lateral migration in linear dunes in Namibia, mapping offset stacks of cross-beds in different directions, indicating repeated lateral shifts in two directions. A recent study in Inner Mongolia observed lateral migration in oblique dunes over a period of 3 years while monitoring an area that had been flattened at the start of the study (Ping et al, 2014).…”
Section: Dating Of Linear Dunesmentioning
confidence: 99%
“…It may be expected that the semi-analytical form drag model is applicable to unidirectional flow over desert sand dunes originated by wind, as these dunes may have the same asymmetric shape as the bedforms considered in this thesis, and may cause flow separation (e.g. Bristow et al, 2000).…”
Section: Bedforms Under Unidirectional Flowmentioning
confidence: 99%